2013
DOI: 10.1590/s1415-52732013000200010
|View full text |Cite
|
Sign up to set email alerts
|

Which equation should be used to measure energy expenditure in HIV-infected patients?

Abstract: OBJECTIVE: In view of the practical need to use equations for the evaluation of energy expenditure in HIV-infected patients, the objective of the present study was to determine the concordance between the energy expenditure values obtained by indirect calorimetry as the gold standard and those obtained by predictive equations elaborated from data for the healthy population: Harris-Benedict, Schofield and Cunningham, and by equations elaborated from data for HIV-infected patients: Melchior (1991-1993). METHODS:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…1,2 It is also present in patients suffering from infectious diseases, such as human immunodeficiency virus and advanced cancers (cachexia). 2,3 This increase in REE (>110% of predicted REE) perpetuates a catabolic state characterized by supraphysiological nutritional requirements, weight loss, muscle atrophy, and the breakdown of adipose depots. 1,4 Systemically, these changes culminate in organ dysfunction and failure, as demon-…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is also present in patients suffering from infectious diseases, such as human immunodeficiency virus and advanced cancers (cachexia). 2,3 This increase in REE (>110% of predicted REE) perpetuates a catabolic state characterized by supraphysiological nutritional requirements, weight loss, muscle atrophy, and the breakdown of adipose depots. 1,4 Systemically, these changes culminate in organ dysfunction and failure, as demon-…”
Section: Introductionmentioning
confidence: 99%
“…Batterham et al noted a low accuracy of REE prediction using different equations in a population of 70 individuals with HIV in Sydney, Australia, and therefore proposed a new equation. Vassimon et al found a strong correlation between the REEm and the results of the equations proposed by Melchior in 1991 and 1993 in 32 Brazilian men.…”
Section: Discussionmentioning
confidence: 89%
“…A lipodistrofia é uma condição multifatorial, e outros fatores podem estar envolvidos na relação entre oxidação de gordura e gasto energético de repouso, incluindo o uso de drogas hipolipemiantes e alterações metabólicas. 36 No estudo Vassimon et al 2013 37 observaram que a maioria das equações preditivas desenvolvidas para a população geral não foi sensível para a estimativa de gasto energético em repouso (GER) em PVHIV brasileiros. Essas equações subestimam o GER comparado aos valores obtidos por calorimetria indireta, ou seja, existe uma falta de concordância das equações.…”
Section: Como a Infecção Prolongada Pelo Hiv + Uso Da Tarv Pode Influunclassified
“…Síndrome de West 157,158,159,160,161,162,163,164 SUS 64,65,109,110,111,118,196,197,198,199,200,201,211,214,216,218 T Técnicas de Genotipagem 58 Tecnologias 187,188,189,190,191,192,194,196,219,231,232 TENS 48,49,50,51,52,53,54,55,56,57,172 Transcraniana 36,37,38 Tratamento 2,3,4,5,6,7,13,15,16,18,…”
mentioning
confidence: 99%